"Person and act" and related essays - John Paul II, Pope, 1920-2005 (The Catholic University of America Press, 2021)
"A new translation, with scholarly notes and textual annotations based on new research into archival collections, of Wojtyla's most well-known philosophical work and related fragments, addresses, and letters"-- Provided by publisher.
Keywords: Act (Philosophy); Personality.; Philosophical anthropology.; Phenomenological anthropology.; Personality; Action (Philosophie); Personnalité.; Anthropologie philosophique.; Anthropologie phénoménologique.; philosophical anthropology.; Phenomenological anthropology; Philosophical anthropology